PERSPECTIVE ARCHITECTURE AND COMPONENTS OF COMPUTER NETWORKS - Yaroslav Nykolaychuk, Yaroslav; Krutskevych, Nazar; Zastavniy, Oleg; Grinchyshyn, Taras (International Journal of Computing, 2014)
This article is about using perspective architecture and components of computer networks will permit to increase productivity and reliability of the specialized computer networks not at the expense of escalating elements of system.